AI Chatbot as a Prompt Generator: A Solution for Enhancing Digital Marketing Campaign Productivity - Buhori; Nanang Hoesen Hidres Abbrori (Universitas Negeri Surabaya, 2025)
This research implements utilization of the artificial intelligence (AI) based chatbots for automatically generating prompt for digital marketing ideas to boost productivity. The interesting results of the study revealed through qualitative methods are that, besides tremendously speeding up the content creation process, chatbots attract a much larger audience. As AI understands the natural language and is processed, the chatbots can help with generating relevant and content ideas in compliance with user needs. This is an alarming discovery that emphasizes how required A.I is as a part of modern marketing strategies as personalization and efficiency are essential for a successful marketing campaign and part of marketing technology stack. The paper further discusses potential challenges like data privacy and algorithmic bias that should be taken into account while using AI. So the created chatbot system will be a sustainable solution. Keywords: AI Chatbot; Generator prompts; Digital marketing; Productivity; Engagement.